Analisis Yuridis terhadap Pengaruh Teknologi Informasi dalam Proses Mediasi di Pengadilan Agama di Indonesia - Naillul Hakim Izzul Anwar; Akhsan Khoirul Anam; Ahmad Baihaq; Muhammad Wildan Hanif; Yowanda Eca Aulia Gunawan; Hifa Taufiqoh; Airin Sabrina Istighfaro (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2026)
The development of information technology has significantly influenced the judicial system in Indonesia, including the mediation process in Religious Courts. The Supreme Court has introduced electronic-based judicial services through e-Court and e-Litigation, allowing case administration and mediation to be conducted online. This study aims to analyze juridically the influence of information technology on the effectiveness of mediation processes in Religious Courts. The research employs a normative legal research method using statutory and conceptual approaches. The legal materials consist of primary sources such as legislation and secondary sources including books and academic journals. The findings indicate that the use of information technology improves time efficiency, accessibility, and transparency in case administration. However, its implementation still faces several challenges, including limited technological infrastructure, low digital literacy, and potential risks to the confidentiality of the mediation process.